“Adhuc in corpore constituto” - Bacon, Benjamin W. (Harvard theological review, 1930)
In my Studies in Matthew (1930, pp. 452 ff.) the reader will find a brief statement of my conviction that the long debated Papias-testimony prefixed by a medieval prologue-writer to the Gospel of John was originally meant for the Revelation. Arguments and references there given need not be repeated here because the present note is concerned only with the final clause of the fragment; but since this is obscure it may be advisable to print it in full side by side with the conjectured original.